Annulated Heterocyclic Derivatives of 1, 3, 6, 8‐Tetraazapyrene (Eur. J. Org. Chem. 24/2013). Issue 24 (13th August 2013) - Martens, Susanne C.; Hahn, Lena; Lombeck, Florian; Rybina, Arina; Wadepohl, Hubert; Gade, Lutz H.
Abstract : The cover picture shows a highly fluorescent polyheterocyclic aromatic compound, dissolved in solvents of varying polarity, which combines the electron‐poor 1, 3, 6, 8‐tetraazapyrene (TAPy) unit with electron‐rich indolizine, thus representing an electronic push–pull system. The HOMO is located on the indolizine part of the molecule, whereas the LUMO primarily resides on the tetraazapyrene unit, which implies considerable intramolecular charge transfer for the corresponding π*←π transition. Such compounds are obtained as side products in the synthesis of a 1, 3, 6, 8‐tetraazapyrene by conversion of the tin "double salt" of tetraaminonaphthalene hydrochloride with trifluoroacetic anhydride in pyridine. Their electro‐ and photochemical properties are discussed in the article by L. H. Gade et al. onpage 5295 ff.